PENGARUH TATA KELOLA PERUSAHAAN, KARAKTERISTIK PERUSAHAAN, DAN RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Ricky Kosasih; Mungniyati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about the effect of corporate governance (managerial ownership, board of independent commissioner, audit committee, institutional ownership), company’s characteristics (firm size, return on equity and board size), and financial ratios which in this research measured by leverage to firm value. Sample used in this research are all manufacturing companies listed in Indonesia Stock Exchange during the research period from 2014 until 2017. Sample selection method used is purposive sampling, in which 64 companies meet the criteria, resulting 256 data are taken as sample. Research data is analyzed by doing hypothesis test using multiple regression method to determine the model of research. The results of this research show that firm size and return on equity affect firm’s value, while managerial ownership board of independent, audit committee, institutional ownership, board size and leverage have no effect to firm’s value.